Electromagnetic absorption behaviors of ferromagnetic Fe-Cr alloy powder and polymer composites in the radio frequency range - Kim, Sang Woo; Lee, Sung Jae (ECO-MATERIALS PROCESSING AND DESIGN VIII, 2007)
In order to achieve effectively high electromagnetic absorption in the radio frequency for the application of the electromagnetic absorber, we investigated annealing effect of microforged powders on electromagnetic absorption behaviors of ferromagnetic Fe-Cr alloy metal powder-polymer composites. The power loss in the far field regime was improved with increasing the microforging time in the frequency range from 50 MHz to near 1 GHz, because the magnetic permeability was slightly increased in the frequency range due to the high aspect ratio of the microforged metal powders. At higher frequency more than similar to 1 GHz, there was no further increased in power loss because of development of internal strain during microforging process. The magnetic permeability was significantly increased with annealing temperature due to the reduction of the lattice strain of the microforged powders. As a result, the electromagnetic absorption of ferromagnetic Fe-Cr alloy metal powder-polymer composites was highly improved.